Regional inequalities and public banks: the role of BNDES in the Brazilian Federation - Colombo, Luciléia Aparecida; Andrade, Thales Haddad Novaes (Universidade Estadual Paulista / UNESP, 2017)
This article intends to analyze how the National Bank for Economic and Social Development (BNDES) acts in the so-called “federative strengthening”, which intends to strengthen the commitment to reduce regional inequalities. As specific objectives, the present study seeks to analyze the regional development programs undertaken by the Bank between 1999 and 2010. We seek to evaluate the extent of these programs in the reduction of regional and federal asymmetries in Brazil, as well as in the economic dynamization of the regions considered less economically developed, such as the North and Northeast of Brazil. Based on these objectives, we intend to verify if the BNDES acts, in fact, to strengthen federative relations, from the programs developed. We also seek to investigate the role that Brazilian federalism plays in regional development financing conditions in Brazil.